2021
DOI: 10.3390/ijms222413209
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Corrosion Evaluation of In Situ Alloyed NiTi Fabricated through Laser Powder Bed Fusion (LPBF)

Abstract: In this work, NiTi alloy parts were fabricated using laser powder bed fusion (LBPF) from pre-alloyed NiTi powder and in situ alloyed pure Ni and Ti powders. Comparative research on the corrosive and biological properties of both studied materials was performed. Electrochemical corrosion tests were carried out in phosphate buffered saline at 37 °C, and the degradation rate of the materials was described based on Ni ion release measurements. Cytotoxicity, bacterial growth, and adhesion to the surface of the fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…The XRD phase analysis did not indicate the presence of TiO 2 . However, it has been shown in our previous study that the thin layer of TiO 2 was found on the material's surface by X-ray photoelectron spectroscopy (XPS) [48]. Since the peaks corresponding to NiTi (B19 ), NiTi 2 and Ni 2 Ti 4 O overlap each other the XRD technique cannot be used alone to determine which phase is present in the studied alloy.…”
Section: Third Heat Treatment-ht3mentioning
confidence: 95%
“…The XRD phase analysis did not indicate the presence of TiO 2 . However, it has been shown in our previous study that the thin layer of TiO 2 was found on the material's surface by X-ray photoelectron spectroscopy (XPS) [48]. Since the peaks corresponding to NiTi (B19 ), NiTi 2 and Ni 2 Ti 4 O overlap each other the XRD technique cannot be used alone to determine which phase is present in the studied alloy.…”
Section: Third Heat Treatment-ht3mentioning
confidence: 95%
“…Here, the corrosion product grows from pit to pit due to the absorption of oxygen by the elemental Ti to form the TiO 2 and TiO 3 product. [32][33][34] In comparison with different corrosion products, Ti oxide requires less driving energy to form a stable product at room temperature. In the region of the NiTi phase, there is no effect of corrosion observed.…”
Section: Morphology Analysis Before and After The Cryo Treatmentmentioning
confidence: 99%
“…One example is the increasing use of 2 additive technologies to produce components in NiTi alloy (nickel-titanium alloys-Nitinol), characterised by unique thermo-mechanical properties. 3D printing of NiTi alloy components opens the way to more advanced applications in various industries and biomedical engineering [10][11][12][13][14]. However, there are also technical challenges associated with 3D printing of NiTi alloys, such as control of the microstructure and mechanical properties, which require further research and technological development.…”
Section: Introductionmentioning
confidence: 99%